Exploring the Language of Flavor: Emotive Language Analysis of Culinary Tourism Promotion in Solo City - Djatmika; Riyadi Santosa; Tri Wiratno; Rara Sugiarti; Agus Hari Wibowo (OKARA: Jurnal Bahasa dan Sastra, 2026)
This study presents a meticulous examination of evaluative language patterns in culinary promotional texts, focusing on the emotive dimensions of communication within the context of Solo City’s culinary tourism discourse. Through a systematic analysis of culinary and restaurant review texts, distinct evaluation patterns and linguistic phenomena are identified and scrutinized. The analysis reveals a predominant emphasis on APPRECIATION aspects, particularly REACTION:IMPACT and REACTION:QUALITY, in conveying evaluations towards culinary entities, highlighting the strategic use of emotive language to captivate reader interest and engagement. However, there exists a notable underutilization of VALUATION aspects, which diminishes the comprehensiveness of the evaluative discourse. Furthermore, the absence of AFFECT and JUDGMENT aspects represents a missed opportunity to enrich the evaluative narrative and build familiarity with readers. Authors adeptly navigate the terrain of evaluative language, employing ATTITUDE aspects such as INTENSIFIERS and ATTITUDINAL LEXIS to imbue their discourse with emotive depth and foster reader engagement. The findings underscore the need for a balanced evaluation approach integrating APPRECIATION, VALUATION, AFFECT, and JUDGMENT aspects to sustain reader interest effectively. Future research directions include exploring cultural influences on evaluative language and investigating linguistic strategies’ effectiveness in culinary promotional texts.